2013
DOI: 10.5539/ijef.v5n7p32
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Value Relevance of Goodwill Impairment Considering Country-Specific Factors: Evidence from EU Listed Companies

Abstract: The objective of this paper is to assess the value relevance of goodwill impairment losses with reference to the listed companies operating in the European Union area during the period from 2008 to 2011. We investigate whether the information of goodwill impairment is a relevant factor that influences the investment decisions of market operators, testing the statistical significance and the explanatory power of a multivariate regression model widely known in literature for estimating market stock prices of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…The variables from 29 to 31 instead are country-specific factors, some of which have been determined following an approach that, to the extent of our knowledge, has not been used in previous studies for predicting bankruptcy. Similar research on this topic can be found in Laghi et al (2013) and Lam (2004).…”
Section: Datamentioning
confidence: 48%
“…The variables from 29 to 31 instead are country-specific factors, some of which have been determined following an approach that, to the extent of our knowledge, has not been used in previous studies for predicting bankruptcy. Similar research on this topic can be found in Laghi et al (2013) and Lam (2004).…”
Section: Datamentioning
confidence: 48%
“…In fact, standard setters decided to move from amortisation to impairment because the latter is expected to provide more appropriate accounting information compared with the former. Nevertheless, findings do not provide a clear evidence: for example, a recent study concerning listed firms of several European countries (Laghi et al 2013) highlights that goodwill impairment is significant only for two years out of the four investigated, while according to other research (Morricone et al 2009) the reliability of the impairment test in context with weaker corporate governance (they investigated Italian listed firms) could lead to more opportunistic behaviour than those characterising the amortisation era.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 88%
“…() examine the economic consequences of IFRS adoption for UK firms and find that mandatory IFRS adoption may benefit some firms but harm others. One can argue that IFRS fair value items are uninformative and misleading for investors; hence, adjustments are necessary to improve the informativeness; however, as the authors point out, studies provide evidence that fair value measurements (Barth and Clinch, ; Landsman et al ., ) and impairments (AbuGhazaleh et al ., ; Amel‐Zadeh et al ., ; Laghi et al ., ) have information content. If so, then the adjustments can be opportunistic.…”
Section: Research Question 1: Fair Value Items and Non‐gaap Earnings mentioning
confidence: 99%